Positive Systems Theory and Applications (POSTA 2016) Rome, Italy, September 14-16, 2016 - Cacace, Filippo; Farina, Lorenzo; Setola, Roberto; Germani, Alfredo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book presents high-quality original contributions on positive systems, including topics such as: monotone dynamical systems in mathematical biology and game theory; mathematical developments for networked systems in biology, chemistry and the social sciences; linear and nonlinear positive operators; dynamical analysis, observation and control of positive distributed parameter systems; stochastic realization theory; biological systems with positive variables and positive controls; iterated function systems; nonnegative dynamic processes; and dimensioning problems for collaborative systems. The book comprises a selection of the best papers presented at the POSTA 2016, the 5th International Symposium on Positive Systems, which was held in Rome, Italy, in September 2016. This conference series represents a targeted response to the growing need for research that reports on and critically discusses a wide range of topics concerning the theory and applications of positive systems.
Persistence, periodicity and privacy for positive systems in epidemiology and elsewhere -- Control of anesthesia based on singularly perturbed model -- Interval observers for SIR epidemic models subject to uncertain seasonality -- Analysis of a reaction-diffusion epidemic model -- On Feedback Transformation and Integral Input-to-State Stability in Designing Robust Interval Observers for Control Systems -- Stability Analysis of Neutral Type Time-Delay Positive Systems -- Internally Positive Representations and Stability Analysis of Linear Delay Systems with Multiple Time-Varying Delays -- On robust pseudo state estimation of fractional order systems -- Analysis of the positivity and stability of fractional discrete-time nonlinear systems -- Continuous-time Compartmental Switched Systems -- Improved controller design for positive systems and its application to positive switched systems.
Keywords: Control engineering; Multibody systems; Vibration; Mechanics, Applied; Dynamical systems; System theory; Control theory; Game theory; Control and Systems Theory; Multibody Systems and Mechanical Vibrations; Dynamical Systems; Systems Theory, Control; Game Theory